Dunja Evers : Constellations. - Fotomuseum Winterthur; Kunstmuseum Bonn; Kunstverein Göttingen (Göttingen : Steidl Publishers Göttingen, 2001)
Dunja Evers has developed a unique picture form which mediates between film, photography and painting. With her works she directs the eye away from the documentary function of photography towards a picture-artistic structuring. Her fragile pictures are photographic paintings which cross all borders of genre. At first, they appear as an almost monochrome kaleidoscope of colours. The colour is underlaid with shadowy, filmically or photographically generated signs which disclose themselves only gradually while being looked at. Stretched space, stretched time appears - and disappears again.
biog. p. 94, ind. tent., gr. tent. p. 95, bibliog. p. 96
Duits
Engels
Dunja Evers : Constellations / Zustände, Fotomuseum Winterthur, 9. November 2001- 6. Januar 2002 / Kunstmuseum Bonn, 7. März - 26. Mai 2002 / Kunstverein Göttingen, 9. Juni - 21. Juli 2002
boek
Keywords: Evers, Dunja